Urban Consumer Market Segmentation: A Study for Brand and Lifestyle Preferences Using The K-Means Clustering - Dwirahmawati, Retno; Nugraha, Yudi; Threezardi, Ricki; Haikal, Jerry (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This research to identify and analyze urban consumer market segments based on their brand and lifestyle preferences by using the K-Means Clustering algorithm. Data processing is assisted by the application of Python 3. With high technology adoption, urban consumers exhibit strong reliance on digital platforms for convenience and efficiency, including e-commerce (Shopee, Tokopedia), digital payments (QRIS), and on-demand transport/delivery services (Grab/Gojek). Consumers within these segments highly value product quality, reflecting a smart and rational purchasing approach, driven by both essential needs and the desire for personal satisfaction. Despite showing significant preference for established, prestigious, and high-quality global brands (such as Adidas, Rolex, Gucci, Tag Heuer, Nike), there is also consistent strong support for local brands, indicating a balance between global appeal and an appreciation for domestic products or authentic values. An active and health-conscious lifestyle is also characteristic, with interests in sports, running, and travel. Furthermore, preferences for complex and luxurious fragrance aromas (Musky Powdery Floral, Floral Vanilla, Citrus Aromatic, Oud Woody Smoky) highlight refined tastes and attention to personal appearance. Social media activity also indicates that urban consumers are an easily reachable audience influenced by digital trends. The findings of this study reveal diverse consumer segments, each exhibiting distinct patterns in demographics, occupation, income, hobbies, and shopping behavior. The first cluster,